Fatty acids increase hepatitis B virus X protein stabilization and HBx‐induced inflammatory gene expression. (7th April 2014) - Cho, Hyun Kook; Kim, So Young; Yoo, Seong Keun; Choi, Yung Hyun; Cheong, JaeHun
<x xml:space="preserve">Abstract</x> The protein level of human hepatitis B virus (HBV) in infection is variable, depending on patient context. We previously reported that HBV X protein (HBx) induces hepatic lipid accumulation and inflammation. Here, we show that abnormal levels of hepatic fatty acids increase HBx protein stability during HBV expression, resulting in the potentiation of HBx‐induced inflammation. Reactive oxygen species, Ca2+ signaling and expression levels of various lipid metabolic genes were investigated in HBx‐expressing cells and in HBx transgenic mice. Fatty acids, including palmitate, stearate and oleate, increased HBx protein stability by preventing proteasome‐dependent degradation. Hepatic inflammation induced by a high fat diet (HFD) and HBx was measured based on the expression of interleukin–6 and tumor necrosis factor α. In addition, the protein level of HBx increased in HFD–HBx transgenic mice. Reactive oxygen species production and intracellular Ca2+ signal activation play critical roles in fatty‐acid‐induced HBx stabilization. Abnormal levels of hepatic fatty acids resulted in synergistic induction of HBx protein and liver inflammatory gene expression through HBx protein stabilization. These results indicate that different fatty acid levels in the liver might affect HBV‐induced pathogenesis.